(De)futuring democracy: Labs, playgrounds, and ateliers as democratic innovations. (December 2021) - Asenbaum (lead author), Hans; Hanusch, Frederic
Highlights: The article fills a gap in the democratic innovations literature, which has so far not examined new lab formats, such as policy labs. Labs are torn between the logic of democratic agency and technocratic control, which is indicative of a likely future of democracy. The article introduces a proposal for two novel formats of democratic innovations: democratic playgrounds and democratic ateliers. In contrast to planning and design, the article makes the case for democratic serendipity as an open-ended, playful exploration. Abstract: New laboratory formats worldwide, including policy labs, innovation labs, and living labs, invite political engagement of multiple stakeholders. Although this format shares the basic characteristics with democratic innovations such as citizens' assemblies, it has yet to be acknowledged by this field of study. This article fills this gap. It finds that labs are torn between the logic of democratic agency and technocratic control, and argues that this power nexus is indicative of a likely future of democracy. Beyond this ambiguous character, labs point to playfulness and creativity as two aspects that established democratic innovations rarely incorporate. Hence, we extrapolate these two aspects to propose alternative formats: democratic playgrounds and democratic ateliers. Instead of the output-orientation of democratic innovations for expected change, playgrounds and ateliers follow the logic of democratic serendipity, an exploratory, open-ended mode of participatory engagement, which promises to open democracy for unexpected change.